Long Mu Qing Xin mixture improves behavioral performance in spontaneously hypertensive rats (SHR/NCrl) by upregulating catecholamine neurotransmitters in prefrontal cortex and striatum via DRD1/cAMP/PKA-CREB signaling pathway - Li, Xuejun; Xiao, Zhen; Jiang, Zhiyan; Pu, Wenyan; Chen, Xiufeng; Wang, Shumin; Liu, Anqi; Zhang, Hongyu; Xu, Zihao (Frontiers in Pharmacology, 2024)
Background: Attention deficit hyperactivity disorder (ADHD), a prevalent neurodevelopmental disorder in children, can be effectively alleviated by the herbal preparation Long Mu Qing Xin Mixture (LMQXM), but its mechanism has not been fully elucidated.Objective: To scrutinize the potential pharmacological mechanisms by which LMQXM improves behavior in spontaneously hypertensive rats (SHR/NCrl).Methods: The SHR/NCrl rats were randomly stratified into the model (SHR) group, the methylphenidate hydrochloride (MPH) group, and groups subjected to varying dosages of LMQXM into the medium dose (MD) group with a clinically effective dose, the low dose (LD) group with 0.5 times the clinically effective dose, and high dose (HD) group with 2 times the clinically effective dose. Furthermore, the WKY/NCrl rats constituted the control group. The evaluation of behavior involved the open field test and the Morris water maze test. HPLC, LC-MS, ELISA, immunohistochemistry, Western blot, and RT-qPCR were utilized to scrutinize the catecholamine neurotransmitter content and the expression of proteins and genes associated with the dopamine receptor D1 (DRD1)/cAMP/protein kinase A (PKA)-cAMP response element-binding (CREB) pathway in prefrontal cortex (PFC) and striatum.Results: MPH and LMQXM ameliorated hyperactivity and learning and memory deficits of SHR/NCrl rats. Among them, LMQXM-MD and MPH also upregulated dopamine (DA), norepinephrine (NE), adenylate cyclase (AC) and cAMP levels, and the expression of proteins and genes associated with the DRD1/cAMP/PKA-CREB pathway in PFC and striatum of SHR/NCrl rats. PFC and striatum DA levels were also upregulated in the LMQXM-LD group as well as the striatum DA levels in the LMQXM-HD group, but there were no statistically significant differences in their NE levels compared to the SHR group. LMQXM-LD and LMQXM-HD also upregulated some DRD1/cAMP/PKA-CREB pathway-related proteins and gene expression, but the effects were discernibly disparate in PFC and striatum. Upon comprehensive analysis, LMQXM-MD appeared to be the most effective dose.Conclusions: Our study tentatively suggests that LMQXM may rectify hyperactivity and learning and memory deficits of SHR/NCrl rats by elevating catecholamine neurotransmitters in the PFC and striatum. This effect may be attributed to the potential activation of the DRD1/cAMP/PKA-CREB signaling pathway, which appears to achieve an optimal response at moderate doses.